Generation tourism: towards a common identity - Filep, S.; Hughes, Michael; Mostafanezhad, M.; Wheeler, F. (Channel View Publications, 2013)
The purpose of this article is to highlight the implications of the indiscipline of tourism academia for a new generation of tourism academics. Generation Tourism is characterised by scholars with a multi-disciplinary education associated with a broad field of study and commonly considered to lack the advantages of a discipline-focused education with its strong theoretical and methodological foundations. The problem this article addresses relates to how new generations of scholars and their views on knowledge creation achieve ascendancy in ways that move on from existing paradigms and earlier cohorts of scholars. Our main argument is that Generation Tourism scholars would benefit from a more clearly developed and common academic identity. To begin the critical conversation around the identity of Generation Tourism we outline five possible points of departure. These points are: (1) learning from historical developments in parent disciplines; (2) spearheading inter-disciplinary scholarship; (3) working towards theoretical developments; (4) embracing mediating methodologies and (5) forming tourism nodes and networks. Recognising these as starting points rather than final statements, we hope that the conversation about Generation Tourism identity will continue in other forums.